Copulas Originating From The Imperative Of 'see/Look' Verbs In Mande Languages - Creissels, Denis (My University, 2017)
This paper analyzes Mande data that suggest a grammaticalization path leading from the imperative of ‘see/look’ verbs to ostensive predicators (i.e. words functionally similar to French voici, Italian ecco, or Russian vot), and further to copulas. Clear cases of copulas cognate with ‘see/look’ verbs are found in several branches of the Mande family, and there is convincing evidence that they did not develop from the semantic bleaching of forms originally meaning ‘is seen/found’ (another plausible grammaticalization path leading from ‘see’ verbs to copulas), but from the routinization of the ostensive use of the imperative of ‘see/look’. Comparison of the Mande data with the Arabic data provided by Taine-Cheikh (2013) shows however that this is not the only possibility for imperatives of ‘see/look’ verbs to grammaticalize into copulas, since in the Arabic varieties in which the imperative form of ‘see’ has become a plain copula, the most plausible explanation is that a modal/discursive particle resulting from the grammaticalization of the imperative of ‘see’ has undergone a process of semantic bleaching in the context of an equative or locational predicative construction that initially included no overt predicator.
Keywords: Mande languages; Copulas; verbs